Effect of Iron Supplementation on Haemoglobin Levels in Anaemic Children of 2–5 Years Age Group - Sattar, Shamima; Quddus, A S M Ruhul (Community Based Medical Journal, 2025)
Iron-deficiency anaemia is a major health issue among young children in low-resource settings, contributing to developmental delays and increased morbidity. A randomized controlled trial was conducted at Community Based Medical College, Bangladesh (CBMC,B), Mymensingh, Bangladesh, from January 2022 to December 2023, to assess the effect of iron supplementation on haemoglobin levels in anaemic children of 2–5 years age group. A total of 60 anaemic children with haemoglobin <11 g/dL was selected for this study. Participants were randomly allocated to either an intervention group (n=30) receiving daily oral ferrous sulfate (3 mg elemental iron/kg/day) or a control group (n=30) receiving standard care without iron supplements. Haemoglobin levels were measured at baseline and post-intervention using standardized cyanmethemoglobin methods. Anthropometric measurements and adverse effects were monitored throughout the study period. The intervention group demonstrated a significant increase in mean haemoglobin levels from 8.7±0.8 g/dL to 11.0±1.1 g/dL (p<0.001). In contrast, minimal change was observed in control group (8.8±0.9 g/dL to 8.9±0.7 g/dL; p>0.05). Adherence to supplementation was observed in 86.7%; only 5(16.7%) mild transient side effects were reported. Children with severe anaemia (haemoglobin <8 g/dL) showed a greater response (2.8 g/dL increase) than those with moderate anaemia (1.9 g/dL increase). Serum ferritin levels increased significantly in the supplemented group (from 14.3±3.0 μg/L to 32.5±5.6 μg/L; p<0.001); however, no difference was observed in control group (from 15.0±2.8 μg/L to 15.8±3.1 μg/L; p>0.05). Our data suggests that adding an iron supplement for 12 weeks significantly improved haemoglobin levels in anaemic pre-school children, with good tolerability and adherence. CBMJ 2025 July: vol. 14 no. 02 P:71-75